Comparative Analysis of Waqf Institutions Governance in India and Singapore - Owais, Mohd; Abdul Manaf, Zati Ilham (El-Barka Journal of Islamic Economics and Business, 2023)
Waqf refers to a specific form of philanthropic charitable act that is practiced by allocating a non-perishable tangible asset. It involves designating categories of beneficiaries who are entitled to receive its benefits or income. This research investigates the governing structures of Waqf institutions in India and Singapore, with the objective of comprehending the intricate factors that influence their operational functionality. This research aims to explore the differences and similarities in the governance structures of waqf in both countries, considering its significance in their socio-religious landscapes. The main objectives of this comparative analysis are to examine the governance models of Waqf institutions in India and Singapore, identify regulatory mechanisms, and evaluate their impact on the administration and utilization of Waqf assets. Additionally, the study aims to illuminate the socio-economic implications of the differences in governance and assess the effectiveness of each model in preserving the intended socio-religious goals of Waqf endowments. This paper is grounded on research conducted using available written materials, and it embraces the qualitative research framework to analyze the literature at hand. By assessing and comparing the governance of Waqf institutions in India and Singapore, significant disparities are uncovered. India's approach is characterized by decentralization and the existence of various regulatory bodies, Singapore adopts a more centralized approach. The study sheds light on how different governance structures impact the effectiveness, transparency, and sustainable management of Waqf assets. Financial sustainability, community involvement, and adherence to socio-religious purpose emerge as pivotal factors that differentiate the two models.